Multinational Enterprise, Political Risk and Organisational Change From Total War to Cold War - Forbes, Neil; Kurosawa, Takafumi; Wubs, Ben (Taylor & Francis, 2019)
Multinationals, Organizational Change, Total War, War and Industry, Business History, Accounting History, Cold War, Organizational Innovation